An Analysis of English Reading Comprehension Performance in Entrance Exams at SBBU University, Pakistan: A Quantitative Study - Rasheeda Rahu; Dr. Sanaullah Ansari (Indus Journal of Social Sciences, 2025)
This paper focuses on the English reading comprehension abilities of 200 candidates who applied at SBBU University in Pakistan through entrance test. Using a quantitative research approach, the study examines students’ reading comprehension exam results to determine performance patterns across literal, inferential, and critical comprehension categories. The results show that Business Administration students outperformed Social Sciences students, with the latter encountering considerable difficulty in higher-order comprehension skills. While female applicants outperformed males somewhat, both genders faced difficulty with inferential and critical reading. The findings underscore the importance of tailored preparatory programs to improve reading competency, particularly advanced comprehension skills, resulting in higher academic outcomes for prospective students.